Subsidies for Higher Education - Johnson, George E. (Journal of Labor Economics, 1984)
Who should pay the resource costs of higher education? This paper investigates a simple model of the general equilibrium of the labor market with three skill levels. Those in the population with the lower level of intelligence and/or sophistication can only become low-skilled workers, but the brighter segment of the population can become either high- or medium-skilled workers. Given the tax structure, the welfare of each group is maximized by a unique subsidy rate on the cost of training high-skilled workers. Under several circumstances, the lower IQ group wants a higher subsidy rate than will the group that benefits directly from the training.